Introduction to polymer rheology - Shaw, Montgomery T. (Wiley, 2012)
"Providing new students and practitioners with an easy-to-understand introduction to the theory and practice an often complicated subject, Introduction to Polymer Rheology incorporates worked problems and problems with appended answers to provide opportunities for review and further learning of more advanced concepts. By limiting the use of mathematics within an approachable format, this introductory overview ensures practicing scientists and engineers understand the concepts underlying the flow behavior of polymer melts, solutions, and suspensions, and are able to interpret experimental data correctly and provide additional insight on a process"--